Enterococcus spp. have higher fitness for survival, in a pH‐dependent manner, in pancreatic juice among duodenal bacterial flora. Issue 1 (5th January 2022) - Itoyama, Saki; Noda, Emika; Takamatsu, Shinji; Kondo, Jumpei; Kawaguchi, Rui; Shimosaka, Munefumi; Fukuoka, Tomoya; Motooka, Daisuke; Nakamura, Shota; Tanemura, Masahiro; Mitsufuji, Suguru; Iwagami, Yoshifumi; et al.
Abstract: Background and Aim: Bacterial infection is involved in the progression of many gastrointestinal diseases, including those of pancreas; however, how and which bacteria colonize in pancreatic juice and tissue have yet to be elucidated. Recently, we reported that Enterococcus faecalis exists in the pancreatic juice and tissues of patients with chronic pancreatic disease. Here, we investigated the survival of E. faecalis in duodenal juice with different pH conditions. Methods: Pancreatic juice samples from 62 patients with cancers of the duodeno‐pancreato‐biliary region were evaluated for the presence of E. faecalis . 16S ribosomal RNA polymerase chain reaction and 16S‐based metagenome analyses were performed to determine the bacterial composition. The survival of E. faecalis in various pancreatic juice conditions was evaluated. Results: Of 62 samples, 27% (17/62) were positive for Enterococcus spp., among which 71% (12/17) contained E. faecalis . Enterococcus spp. showed the highest fitness for survival in alkaline pancreatic juice among various bacterial species. The microbiome of pancreatic juice from patients with pancreatic and bile duct cancer showed diversity, but Enterococcus spp. were enriched among duodenal tumors and intraductal papillary mucinous neoplasms. Conclusions: Alkalinity is one of the important factors for the selective survival of E. faecalis among microbiota. E. faecalis can colonize the pancreatic duct when the pancreatic juice condition is altered. Abstract : Enterococcus spp. have higher fitness to survive in pancreatic juice. Enterococcus spp. can colonize pancreatic juice at subphysiological pH levels. Enterococcus spp. are enriched in the pancreatic juice of patients with intact ductal flow.